ANALISIS UNSUR INTRINSIK NOVEL “5cm” KARYA DONNY DHIRGANTORO - Dini Indriati; Teti Sobari; Mimin Sahmini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This novel analysis aims to describe the intrinsic elements contained in the “5cm” novel of Donny Dhirgantoro. The data source in this study is a “5cm” novel of  Donny Dhirgantoro. The method used in this research is the qualitative descriptive method. The result of this study indicate that the “5cm” nivel of Donny Dhirgantoro has a theme of friendship, love, and trust in the dreams of characters in the novel. The characters in this novel are different that makes it interesting to read, using a mixture plot, with a place, atmosphere, and social background. The point of view used is a third omniscient and the there is a mandate, that is to be humans must have a strong belief accompained by hard work that will give what kind of results we dream of.